Establishment of nutrient sufficiency ranges in olive using boundary-line approach - Ali, Ali M. (Journal of plant nutrition, 2023)
The establishment of optimum nutrient concentrations provides excellent knowledge for the diagnosis and correction of plant nutritional status to maximize yield. This study was conducted to determine the optimum values and sufficiency ranges of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), manganese (Mn), zinc (Zn), and copper (Cu) in olive trees grown in various land forms in Egypt by boundary-line approach. Over two consecutive years, foliar samples from 266 olive trees were collected from different growing areas in Egypt and fruit yields per tree were reported. The derived optimum concentrations for these nutrients by solving the first derivation of the inferred second-degree polynomial functions of the relationship between fruit yield and leaf nutrient concentrations were 1.54% for N, 0.19% for P, 0.87% for K, 1.48% for Ca, 0.22% for Mg, 125 ppm for Fe, 33.7 ppm for Mn, 23.5 ppm for Zn, and 8.6 ppm for Cu. Sufficiency ranges corresponding to 90% of the maximum fruit yield were 1.29%-1.80%, 0.14%-0.24%, 0.66%-1.08%, 1.09%-1.90%, 0.10%-0.33%, 63-165 ppm, 30.2-35.9 ppm, 16.6-30.2 ppm, and 2.8-13.9 ppm, respectively. Since standards of optimum nutrition are not readily available in Egypt and in similar places, the current study provides an important guideline for diagnosing olive trees nutritional status.